John Wick. Chapter 2 [videorecording (DVD)] - Reeves, Keanu; McShane, Ian, 1942-; Leguizamo, John (Lionsgate, 2017)
In this next chapter following the 2014 hit, legendary hit man John Wick is forced back out of retirement by a former associate plotting to seize control of a shadowy international assassins' guild. Bound by a blood oath to help him, John travels to Rome where he squares off against some of the world's deadliest killers.